Optimisation of the quality of yellow alkaline noodles using a combination of microwave and pulsed-uv technologies. - Karim, Roselina; Anissa Soraya,; Syed Muhammad, Sharifah Kharidah; Mohamad Ghazali, Farinazleen; Mat Hashim, Dzulkifly; Mohd Adzahan, Noranizan (2012)
This research was conducted to find the optimum treatment using a combination of microwave and pulsed-UV technologies for reducing the initial microorganism load of VAN, and to study the effect of the combination of microwave and pulsed-UV technologies on the textural properties, of YAN. The textural (texture profile analysis) and microbiological (total aerobic mesophilic bacteria, yeast and mould counts) qualities of YAN were :monitored. Post processing decontamination using a combination of microwave and pulsed-UV technologies was, effective in lowering the microorganism load but affected the textural quality of YAN. The optimum conditions for producing YAN with the lowest microbiological count and acceptable textural quality were 5s of microwave heating at 900W and pulse,d':UV treatment at energy level of 3.5J/cm2• A combination of thermal and non thermal technologies i.e. microwave pulse-UV treatment is recommended as an alternative method for extending the shelf life of parboiled yellow alkaline noodles without using chemical preservative.